Changes in Physicochemical Properties and Qualities of Red Brown Rice at Different Storage Temperatures - Tao Wang (MDPI AG, 2021)
The effects of storage temperature on the physicochemical properties and qualities of red brown rice were investigated in this study. The samples were vacuum-packed in nylon/polyethylene pouches and stored at 15 °C, 25 °C and 35 °C for 12 weeks. The moisture content decreased as storage time was prolonged. Rice stored at 15 °C and 25 °C had a lower falling range of water content compared to the samples stored at 35 °C. Free fatty acid values increased fastest when samples were stored at a high temperature, and the rise can be effectively delayed at low temperatures. The pH of residual cooking water and adhesiveness decreased, while the heating water absorption rate and hardness increased during storage for red and brown rice. Low-field nuclear magnetic resonance results indicate that water molecules migrated, the binding force of H protons became stronger and the bonds between molecules became closer with increased storage duration. Temperature had an obvious correlation with starch granules and protein structure, characterized by a scanning electron microscope and Fourier transform infrared spectroscopy. Low temperatures significantly retarded those changes. The results indicate that storage temperature is a vital factor affecting the physicochemical properties and qualities of red brown rice and provided reference and theoretical basis for the actual storage of red brown rice.